Multidimensional comparative analysis of the number of deaths in Europe between 2018–2021 in terms of economic security - Kozicki, Bartosz; Grabowska, Sabina; Ovsepyan, Arsen; Sowa, Bogdan (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
The study concerned a multidimensional comparative analysis of the number of deaths in 30 European countries between 2018-2021, also by age groups and type of vaccination in Poland in 2021 in terms of the impact of the COVID-19 pandemic and economic security. The data for the research was obtained from the websites of Eurostat and the Central Statistical Office. They were grouped and sorted from largest to smallest. In order to achieve the aim of the study, the death indices were calculated and analyzed. The obtained test results are included in bar charts. The article ends with a summary and final conclusions.

W opracowaniu przeprowadzono wielowymiarową analizę porównawczą liczby zgonów w 30 państwach Europy w latach 2018-2021, a także według grup wiekowych i rodzaju szczepień w Polsce w 2021 roku w aspekcie oddziaływania pandemii COVID-19 i bezpieczeństwa ekonomicznego. Dane do badań pozyskano ze strony internetowej Eurostatu i Głównego Urzędu Statystycznego. Zostały one poddane grupowaniu i porządkowaniu od największych do najmniejszych. Do realizacji celu pracy wyliczono i poddano analizie indeksy zgonów. Uzyskane wyniki badań zawarto na wykresach słupkowych. Artykuł kończy się podsumowaniem i wnioskami końcowymi.
Keywords: human deaths; multidimensional comparative analyzes; security; economic security; COVID-19; zgony ludzi; wielowymiarowe analizy porównawcze; bezpieczeństwo; bezpieczeństwo ekonomiczne